Islamic Da’wah and the Preservation of the Tamil Language - Hakim, Mohammad Andi (Al-I'timad: Jurnal Dakwah dan Pengembangan Masyarakat Islam, 2023)
This research reveals the tradition of Islamic preaching and the contribution of the Tamil language at the Chulia Mosque in building Singapore's religious life. The concept of da'wah and the use of the Tamil language can be used as an example for other mosques in creating an inclusive and welcoming environment for all worshippers.Mosques play a significant role in making Singapore a friendly country for all ethnicities and religions. This research is qualitative in nature with a descriptive qualitative approach through observation and documentation methods. The results of this study focus on two important things; First, the contribution of the mosque in strengthening the tradition of inclusive Islamic da'wah. Second, Singapore's multilingualism through the Tamil language is one of the main factors in building religious harmony in diversity.